Analisa Investasi Sistem Informasi Administrasi Pada Distributor X dengan Menggunakan Metode Information Economics - Imelia Widjanadi; Yulia Kendengis; Leo Willyanto Santoso (Jurnal Infra, 2015)
Nowadays, technology develops very fast.   Especially as a support for business activity, such as administration information system which is already applied by X distributor. There are some elements to be fulfilled in order to apply the technology. However, it is important to calculate the benefits compare to the technology expenses. To help the organization in solving that problem, it needs an Information Economics as a tools to calculate the benefits and the investment.Based on that problem, there must be an analysis on the investment. That analysis can be done by calculating the ROI and IE Score. Then, the result can be a consideration whether the infestation worth to be done or not. The quantification which is divided into four categories, value linking, value acceleration, value restructuring, and innovation valuation and makes a questioner for the weighting to the business and technology domain.Because of the complexity calculation process, there was made a calculating tool which can help the organization easily get the result of ROI and IE Score. That application based on the web which is use a PHP program language and Mysql as its database. It will make the user easily access the application everywhere and every time. The weighted score from the analysis is 82.86. This score was categorized as a very great investment. Moreover, the payback period is a year 5 months and 11 days.